2013
DOI: 10.2106/jbjs.l.00777
|View full text |Cite
|
Sign up to set email alerts
|

The Stabilizing Mechanism of the Latarjet Procedure

Abstract: The Latarjet procedure remains an effective procedure for restoring stability to an unstable glenohumeral joint, particularly when there is glenoid bone deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
219
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(229 citation statements)
references
References 2 publications
1
219
1
8
Order By: Relevance
“…33 The final stabilizing mechanism of the Latarjet procedure is provided by the reconstruction of the glenoid concavity by the coracoid transfer, which contributes a significant portion of glenohumeral stability in the midranges of motion. 32,34 Multiple clinical outcome studies have further confirmed the efficacy of the Latarjet procedure's ability to restore glenohumeral stability. Hovelius et al 35 reported a 3.4% recurrence rate after the Bristow-Latarjet procedure performed in 118 patients at 15-year followup, with a 98% satisfaction rate in their cohort.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…33 The final stabilizing mechanism of the Latarjet procedure is provided by the reconstruction of the glenoid concavity by the coracoid transfer, which contributes a significant portion of glenohumeral stability in the midranges of motion. 32,34 Multiple clinical outcome studies have further confirmed the efficacy of the Latarjet procedure's ability to restore glenohumeral stability. Hovelius et al 35 reported a 3.4% recurrence rate after the Bristow-Latarjet procedure performed in 118 patients at 15-year followup, with a 98% satisfaction rate in their cohort.…”
Section: Discussionmentioning
confidence: 94%
“…Three distinct mechanisms have been described that contribute to the stability of the Latarjet procedure. 32 The primary stabilizing mechanism, known as the "sling effect," is provided by the conjoint tendon's reinforcement of the dynamic Fig 7. Fastening of preloaded suture washers. After placement of two 3.5-mm cortical or 4.0-mm malleolar screws and washers, preloaded suture washers (Arthrex) (Fig 6) are fastened for coracoid graft fixation in the right shoulder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] The Bristow-Latarjet procedure has been reported to have three stabilizing mechanisms: (i) buttress effect of the coracoid bone; (ii) sling effect of the conjoint tendon and subscabularis; and (iii) reinforcement through an anterior capsular duplication with the released coracoacromial ligament. [17][18][19] However, there are several reported complications, such as bony non-union, progressive impingement and loosening or migration of hardware. 8,9 We consider, particularly in young patients with anterior instability and glenoid bone loss, that the use of screws and permanent alteration of the anatomy should be avoided.…”
Section: Introductionmentioning
confidence: 99%